2017
DOI: 10.1093/infdis/jix129
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Microchimerism Predicts Increased Infection but Decreased Disease due to Plasmodium falciparum During Early Childhood

Abstract: The acquisition of MMc may result in increased malaria infection but protection from malaria disease. Future studies should be directed at the cellular component of MMc, with attention to its ability to directly or indirectly coordinate anti-malarial immune responses in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…A notable finding of this paper is that maternal micro-chimerism was more profound in these preterm babies, thus providing additional evidence of inflammation-driven increase in maternal micro-chimerism. The same authors reported earlier that fetuses with severe congenital diaphragmatic hernia, who exhibit high inflammatory cytokines in cord blood, also have increased maternal micro-chimerism (7); a similar increase was also described in babies exposed to placental malaria (8). Interestingly, the latter study showed that both malaria infection and inflammation contributed to this enhanced transfer of maternal cells.…”
supporting
confidence: 64%
“…A notable finding of this paper is that maternal micro-chimerism was more profound in these preterm babies, thus providing additional evidence of inflammation-driven increase in maternal micro-chimerism. The same authors reported earlier that fetuses with severe congenital diaphragmatic hernia, who exhibit high inflammatory cytokines in cord blood, also have increased maternal micro-chimerism (7); a similar increase was also described in babies exposed to placental malaria (8). Interestingly, the latter study showed that both malaria infection and inflammation contributed to this enhanced transfer of maternal cells.…”
supporting
confidence: 64%
“…This may permit larger molecules or even cells to enter into the fetal circulation. 42,48 Once across the syncytiotrophoblast barrier, it is unclear how exogenous antigens traverse the fetal endothelium, which represents the last barrier to entry into the fetal bloodstream, although FcgRI on endothelial cells could play a role. Presumably, malaria antigens and/ or immune complexes are subsequently taken up by fetal APCs, although this process has received little or no research attention.…”
Section: Mal Aria Anti G En E Xp Osure I N Uteromentioning
confidence: 99%
“…54 PM has been associated with higher levels of maternal microchimerism in cord blood, particularly when placental histopathology shows evidence of significant inflammation. 48 The short-and long-term consequences of this maternal microchimerism for infant immunity have not yet been fully explored, but increased induction of T regs during gestation could lead to dampened pathogen-specific immunity. It has also been noted that cord blood immune cell populations, including T-cells, B-cells, NK cells, and monocytes frequently include cells of maternal origin, which are particularly enriched among memory T-cells.…”
Section: Pl Acental Mal Aria and Maternal Microchimeris Mmentioning
confidence: 99%
“…Based on the hypothesis that malaria infection results in inflammation and pathologic changes as well as alterations in VEGF expression in the placenta, the association between PM and maternal microchimerism was recently examined . The investigators found that inflammatory PM was associated with an increased prevalence of maternal microchimerism and that both inflammatory and noninflammatory PM were associated with increased level of maternal microchimerism.…”
Section: Maternal Malaria Shapes the Maternal To Foetal Graftmentioning
confidence: 99%